2016
DOI: 10.15376/biores.11.3.7476-7489
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Hazelnut Husk in Recycled High-Density Polyethylene Composites

Abstract: Hazelnut husk was considered as a potential filler for thermoplastic composites. Different amounts of hazelnut husk flour and the recycled high-density polyethylene (R-HDPE) were used as the filler and polymer matrix, respectively. The composite compounds were produced using single-screw extrusion compounding, and then composite panels were prepared by hot-press compression molding. The morphological, physical, mechanical, and thermal properties, as well as the biological durability of the composites, were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…Bu çalışma, bazı tarımsal atıklardan elde edilen kompozitlerin esmer çürüklük mantarına (Fomitopsis palustris) karşı dayanıklılığını tespit etmek için yapılmıştır. Tarımsal atıkların plastik kompozitlere takviye elemanı olarak kullanıldığı birçok çalışma ve çürüklük testleri mevcuttur [5], [6], [7]. Ancak yonga levhaya takviye materyal olarak veya tamamen bu tarımsal atıklardan üretilerek çürüklük testleri G yapılan çalışmalar sınırlıdır.…”
Section: Abstract: Brown Rot Fomitopsis Palustris Composite Agricuunclassified
“…Bu çalışma, bazı tarımsal atıklardan elde edilen kompozitlerin esmer çürüklük mantarına (Fomitopsis palustris) karşı dayanıklılığını tespit etmek için yapılmıştır. Tarımsal atıkların plastik kompozitlere takviye elemanı olarak kullanıldığı birçok çalışma ve çürüklük testleri mevcuttur [5], [6], [7]. Ancak yonga levhaya takviye materyal olarak veya tamamen bu tarımsal atıklardan üretilerek çürüklük testleri G yapılan çalışmalar sınırlıdır.…”
Section: Abstract: Brown Rot Fomitopsis Palustris Composite Agricuunclassified
“…[28][29][30][36][37][38] Similar results were obtained by Tufan et al and by Wang et al who also noted an increase in the crystallinity of wood after heat treatment. [39,40] In many works paid special attention to issues related to strength properties, however, their results made a lot of controversy. On the one hand, a lot of the scientific papers confirm the positive effect of using this type of modification on mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Tufan et al noted that the thermal modification of wood significantly reduces tensile and flexural strength. [ 39 ] In addition, in the work of Yang et al, it turned out that the use of this type of modification in a wide temperature range did not cause a large difference in strength properties compared to systems with unmodified filler. [ 44 ] The results obtained by Xu et al indicated that the dimension stability improved while the mechanical properties decreased after thermal modification.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature data, the lignocellulosic materials used as fillers are classified according to their origin and botanical functions, including bast, leaves, seeds, fruit, wood, stems and grasses [33,34]. Additionally, technological waste from the food industry can also be used, for example, crushed walnut shells [35,36], hazelnut [37] and peanut [36], coffee grounds [26], rice bran [36,38] and wheat [30,39] or sugar cane bagasse [40].…”
Section: Introductionmentioning
confidence: 99%